Copyright Protection of Podcast-Based Audiobooks Adapted by Third Party Without Permission on Digital Platform Based on Indonesian Positive Law - Salma Alifya Khairunnisa; Rika Ratna Permata; Sudaryat Sudaryat (Widya Yuridika, 2023)
Podcasts are basically digital audio content that is much loved by the public and audiobooks become one of the contents that have recently been incorporated into podcast content on a digital platform. The presence of this podcast-based audiobook raises a new problem in copyright related to its adaptation. This study aims to examine legal protection regarding podcast-based audiobooks from the perspective of copyright based on Indonesian Copyright Law and ITE Law. Furthermore, this study was also conducted to analyze the act of adapting books into podcast-based audiobooks on a digital platform carried out by content creators without the permission of the creators or copyright holders. This study uses normative juridical approach with descriptive specifications. The normative juridical approach is carried out by exploring legal theories and principles as well as applicable laws and regulations. This study describes legal problems that occur in society and is analyzed based on the applicable laws and regulations. The result of the study shows that copyright protection for podcast-based audiobook content has been regulated in several articles in the Copyright Law, including Article 40 paragraph (1) and Article 9 paragraph (1) regarding the right to adapt a creation. In addition, the act of adapting and uploading without permits made by content creators on a digital platform is considered to have violated the provisions of Article 9 of the Copyright Law and Article 25 of the ITE Law.